The PAH patient's perspective - Daniel A. Jeffery; Wendy Gin-Sing; Radwa Bedair; Luke S. Howard (International Journal of Cardiology Congenital Heart Disease)
Pulmonary Hypertension is a serious condition which can occur in adults living with congenital heart disease. Due to advances in the care of patients with congenital heart disease, patients are living longer with the condition. Unfortunately, patients living with Pulmonary Arterial Hypertension associated with Congenital Heart Disease (PAH-CHD) face a number of different issues directly related to their condition, which range from physical limitations and uncertainty over their diagnosis, which in some cases cause significant depression and anxiety, to impact on their relationships with friends and family, financial challenges and family planning.In this article, we interview two patients living with PAH-CHD and discuss the numerous issues that patients may face as a direct result of their condition.